Surface Hydrocarbons from the Leaves of Portulaca oleracea Linn - Laskar, Subrata; Banerjee, Gautam; Mukherjee, Ambarish (Asian Journal of Chemistry, 2010)
Surface hydrocarbons from the fresh leaves of Portulaca oleracea Linn. have been characterized and their relative distribution determined through GLC studies. The considerable occurrence of branched chain hydrocarbons may be an indication of the characteristics of lower plant based on taxonomy.